An aging India : perspectives, prospects, and policies - Liebig, Phoebe S.; Rajan, S. Irudaya (Sebastian Irudaya), 1959- (Journal of aging & social policy ;, 2015)
Explore Indian policy and practice on aging from a variety of perspectives! This pathbreaking collection provides something that has been missing in the literature on aging in India, especially for non-Indian audiences: studies of various aspects of aging in India combined with analyses of current policies, policy trends and recommendations. You'll examine aging issues from a variety of perspectives?demographic foundations, social and family relations, economics, health and disability, current interventions, and advocacy and policy. An Aging India also provides you with up-to-date ref.